"Hell on Earth": Single mothers' experiences of temporary accommodation in London and its impact on their mental health. Issue 4 (2nd October 2022) - Carey, Nina; Karwatzki, Emma; Griffin, Vanessa; Keville, Saskia
ABSTRACT: Working therapeutically in the United Kingdom, means working with individuals made homeless by a housing crisis created by economics and policy decisions. Negative effects are often experienced by the most vulnerable with subsequent injustices concealed by those at the top; this has been conceptualised as a structural violence. Whilst the mental health of homeless single mothers and their children is disproportionately affected, research on structural inequality is minimal and neglects lived experience. Semi-structured interviews with 12 single mothers living in temporary accommodation in London were analysed using Thematic Analysis. Four main themes emerged: 'Neglect and abuse within a powerful, unjust system', 'Futility, entrapment and cycles of suffering', 'Mothering against the odds', and 'Surviving and resisting in the face of adversity'. Results highlighted the distress temporary accommodation created for mothers and children. Despite this, love and care were evident within mother-child relationships. Through individual and collective action, mothers strove to resist the sources of their distress, even whilst facing adversity and stigma, providing insight for therapists on the operation of structural violence. Social action psychotherapy provides a collective approach addressing experiences of stigma and material inequalities where professionals can acknowledge the reality of oppression and stand in solidarity to resist it.